2013
DOI: 10.5572/kosae.2013.29.6.818
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Characteristics of Rainwater at Jeju Island during 2009~2010

Abstract: The collection of rainwater samples was made at Jeju area during 2009~2010, and the major ionic species were analyzed. In the comparison of ion balance, conductivity, and acid fraction for the validation of analytical data, the correlation coefficients showed a good linear relationship within the range of 0.966~0.990. The volume-weighted mean pH and electric conductivity were 4.9 and 17.8 μS/cm, respectively, at the Jeju area. The volume-weighted mean concentrations of ionic species in rainwater were in the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Edmonds et al (1991) [45] suggested that anion deficit means of the amount of unmeasured organic acids. Kim et al (2013) [32] found that the organic acids (CH3COO …”
Section: Quality Assurancementioning
confidence: 99%
See 1 more Smart Citation
“…Edmonds et al (1991) [45] suggested that anion deficit means of the amount of unmeasured organic acids. Kim et al (2013) [32] found that the organic acids (CH3COO …”
Section: Quality Assurancementioning
confidence: 99%
“…Some studies have suggested that air masses from the Asian continent increase the concentration of anthropogenic components of rainwater in Korea [31,32]. Choi et al (2015) [33] studied precipitation chemistry in the area near Shihwa Lake (located in the mid-western area of the Korean peninsula), using both urban and background stations to compare precipitation chemistry.…”
Section: +mentioning
confidence: 99%
“…A portion of each of these samples was tested for pH and electrical conductivity, and analyzed to identify the major ionic components of precipitation. Following the method of Kim et al, 1-2 drops of chloroform were added to the remaining portions of the samples and stored in a freezer at −20 • C, to be used for trace analysis such as organic acid analysis [12].…”
Section: Samplingmentioning
confidence: 99%
“…The transboundary problem caused by the long-range transport of air pollutants is a sensitive dispute between neighboring countries and has extensively been examined using back trajectory analysis [12]. In this study, the movement of air masses at the time of precipitation sampling was estimated using HYSPLIT4.0, based on back trajectory analysis, to establish the inflow path of pollutants to the precipitation.…”
Section: Inflow Path Of Precipitation Componentsmentioning
confidence: 99%
See 1 more Smart Citation